META-ANALYSIS OF THE IMPACT OF TREATMENT BOUQUET FOR METASTATIC BREAST CANCER IN ABUJA, NIGERIA. - Ahmed , Ibrahim; Nwaze, Obini Nweze; Onoka , Chika Christiana; Adehi, Mary Unekwuojo (Economics and Statistics Research Journal (ESRJ), 2025)
This study evaluated the impact of treatment bouquets—a combination of therapeutic modalities on survival rates and adverse reactions in metastatic breast cancer (MBC) patients in Abuja, Nigeria. The primary objective was to assess the efficacy of treatment bouquets in improving survival rates while identifying factors influencing outcomes and adverse reactions. Using a meta-analytic approach, the study synthesizes da/ta from six eligible studies conducted between 2000 and 2022. These studies were selected based on specific inclusion criteria, focusing on MBC patients receiving treatment combinations for a minimum of 5 years. Statistical analysis included random-effects modelling to address the heterogeneity among studies and evaluate the overall impact of these treatments. The findings demonstrate that treatment bouquets significantly enhance survival rates compared with single-treatment modalities. However, their use is associated with increased adverse reactions, including fatigue, neuropathy, and nausea. The results highlight the variability in treatment efficacy and side effects depending on the combinations used and patient-specific factors such as age, comorbidities, and disease progression. The study concludes that while treatment bouquets offer substantial survival benefits, personalised treatment plans are critical to minimise adverse effects and optimise outcomes. It recommends the adoption of multidisciplinary approaches, enhanced monitoring of side effects, and further research to refine treatment combinations. These findings provide valuable evidence for health care professionals and policymakers, contributing to the improved management of MBC in Abuja, Nigeria